Sor Juana Inés de la Cruz: linkage between work and archive in the preliminary texts of her original editions (Anclajes, 2018)
Since the publication of Sor Juana Inés de la Cruz’s Obra Completa between 1951 and 1957, various documents (letters, drafts, minutes and poems) have been found, that challenge the way Alfonso Méndez Plancarte titled his edition. His work, for its part, does not lack issues, given it rearranges Sor Juana’s work, modifying its intra- and intertextual relationships, as well as omitting the original paratexts, with the notable exception of the epigraphs. As for this study, the subject of our analysis will be the loss of documents, the emergence of others, and their relationships with the constitution of an author’s work. Different theories of the archive will be examined to analyze problems of limits, critical interpretations, editions and the peculiar interaction between work and archive in Sor Juana’s paratexts in her original editions (1689, 1692, 1700).
Keywords: Sor Juana Inés de la Cruz; Latin American Colonial Literature; Literary Criticism; XVII Century; Editing